Optical IP switching - Ruffini, Marco (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2008)
Improvements in the optical transmission technology, over the past fifteen years, have substantially facilitated the development and worldwide deployment of the Internet, by reducing the cost of data transport. The exponential growth in Internet traffic however, demands new solutions at the routing layer, as current IP routing technology struggles to deliver the necessary bandwidth at competitive costs.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin